2019
DOI: 10.1021/acs.bioconjchem.9b00645
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Degradation of Inorganic Nanoparticles in Biological Environments

Abstract: In solution, nanoparticles may be conceptually compartmentalized into cores and engineered surface coatings. Recent advances allow for simple and accurate characterization of nanoparticle cores and surface shells. After introduction into a complex biological environment, adsorption of biological molecules to the nanoparticle surface as well as a loss of original surface components occur. Thus, colloidal nanoparticles in the context of the biological environment are hybrid materials with complex structure, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 157 publications
0
22
0
Order By: Relevance
“…[12][13][14][15] However, one major obstacle engineered nanoparticles (including the magnetic ones) still face in their therapeutic mission, concerns a decreased stability and loss of targeting potential in the complex biological environment. [16][17][18][19][20][21] Indeed, despite efforts to customize nanoparticles surface, made with the ambition to deliver nanoparticles to a specific target, the most probable nanoparticles' fate is to end up within endosomes of hepatic and splenic macrophages, where nanoparticles undergo gradual "digestion". Therefore, the topical nano-bio-interface query of the current and following decade relates to processes occurring within the (intra)cellular environment, which profoundly alters the physical and chemical properties of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] However, one major obstacle engineered nanoparticles (including the magnetic ones) still face in their therapeutic mission, concerns a decreased stability and loss of targeting potential in the complex biological environment. [16][17][18][19][20][21] Indeed, despite efforts to customize nanoparticles surface, made with the ambition to deliver nanoparticles to a specific target, the most probable nanoparticles' fate is to end up within endosomes of hepatic and splenic macrophages, where nanoparticles undergo gradual "digestion". Therefore, the topical nano-bio-interface query of the current and following decade relates to processes occurring within the (intra)cellular environment, which profoundly alters the physical and chemical properties of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the early studies evaluating nanoparticles long-term intracellular transformations unanimously lead to the premise that intracellular (endosomal) environment transforms nanoparticles identity. 19,[21][22][23][24][25][26] Finally, while nanotechnology emerged rather recently, magnetic nanoparticles could be traced as far back as Archean, 27 when magnetic particles allowed organisms magnetotaxis along the geomagnetic field. 28 And surprisingly, bacterial cells 29 are not the only ones capable of magnetic bio-mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides that bind on NP surfaces are interesting because they can also be used for biological targeting and may play a role in determining NP biodegradation [52]. Early Figure 2.…”
Section: Inorganic Nanostructure-templating Effects By Peptidesmentioning
confidence: 99%
“…Peptides that bind on NP surfaces are interesting because they can also be used for biological targeting and may play a role in determining NP biodegradation [52]. Early studies identified over 30 peptide sequences able to bind cobalt ions, and nearly 20 that bound silver ions by using phage-display and PCR methods [53].…”
Section: Inorganic Nanostructure-templating Effects By Peptidesmentioning
confidence: 99%
“…Nanomaterials are exciting building blocks of modern science and technology owing to their particular size‐dependent properties. [ 1 ] Noble metal nanoparticles (NPs) have evolved significantly (particularly in terms of surface modifications [ 2 ] ) after the pioneer studies of Faraday's “colloidal gold.” [ 3 ] Controlling the size of NPs is very important to understand the mechanistic details of their interesting properties. Diverse methodologies have been developed to synthesize NPs of controlled sizes.…”
Section: Introductionmentioning
confidence: 99%